Is Visiting the ESB Website Deteriorating the Air Quality of our Countries? A Statistical Analysis of the Relationship Between Air Pollution Levels and Information & Communication Technologies - Katharina Isabella Kühn (Junior Management Science (JUMS), 2021)
Information and communication technology (ICT) is often praised for reducing emissions, however, data centres enabling these technologies have a high energy demand which produces emissions due to CO2-intensive energy production. The purpose of this paper is to investigate whether a relationship between ICT categories and air quality exists and how ICT affects it. This will contribute to a greater understanding of how to mitigate the effect of the rise of new digital technologies. This paper examines the effects of ICT aspects (Knowledge, Technology, Future Readiness) on air quality in 57 countries by using multilinear regression. The results show that a linear relationship between ICT factors and air quality exists. Technology has a negative effect on air quality, whereas Future Readiness has a positive effect. The effect of Future Readiness on air quality is almost twice as high compared to Technology. A relationship between Knowledge and air quality, as proposed in the literature, could not be proven by the model. It can be concluded that this combination of findings provides some support for the conceptual premise that the net effect of ICT on air quality might be positive and that the share of the total carbon footprint of the ICT sector might have been forecasted too high.
Keywords: 650; Information technology; air quality; energy consumption; sustainability